2015
DOI: 10.5901/mjss.2015.v6n6s5p394
|View full text |Cite
|
Sign up to set email alerts
|

Discussion on Religious Practice in Counseling: a Preliminary Survey

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…This finding is in line with a study which found that religion and spirituality play a very important role in human life. Religion plays various roles such as it gives peace of mind, gives strength to face the trial of ill-health, assists in self-transformation, builds positive emotions and reduces feelings of depression (Emlet et al 2018;Van de Velde et al 2017;Carr & Kroth 2017;Wendt et al 2017;Van Cappellen et al 2016;Abdullah et al, 2016;Gopal, 2014;Mokhtar & Albaraka, 2016;Hamjah et al2017;Hamjah & Mohd. Arib, 2015).…”
Section: 73mentioning
confidence: 99%
“…This finding is in line with a study which found that religion and spirituality play a very important role in human life. Religion plays various roles such as it gives peace of mind, gives strength to face the trial of ill-health, assists in self-transformation, builds positive emotions and reduces feelings of depression (Emlet et al 2018;Van de Velde et al 2017;Carr & Kroth 2017;Wendt et al 2017;Van Cappellen et al 2016;Abdullah et al, 2016;Gopal, 2014;Mokhtar & Albaraka, 2016;Hamjah et al2017;Hamjah & Mohd. Arib, 2015).…”
Section: 73mentioning
confidence: 99%
“…Studies in the Western context have shown the need to discuss religious issues in the implementation of guidance and counseling practices (Hamjah & Muhamad Arib, 2015) Worship is one of the important components in the Islamic teachings. The application of worship aspects in guidance and counseling is as important as the implementation of worship in the life of a Muslim.…”
Section: Introductionmentioning
confidence: 99%
“…Among the types of religious practices referred to are salat, reading al-Qur'an, and salawat. The results showed that the implementation of worship in guidance and counseling can be used to support counselees in decision-making process based on Divine values obtained from his spiritual experience (Hamjah & Muhamad Arib, 2015).…”
Section: Introductionmentioning
confidence: 99%